Measuring Quality at the Surgeon Level - Chamely, Elias A.; Stulberg, Jonah J. (Clinics in Colon and Rectal Surgery, 2023)
Patients expect high-quality surgical care and increasingly are looking for ways to assess the quality of the surgeon they are seeing, but quality measurement is often more complicated than one might expect. Measurement of individual surgeon quality in a manner that allows for comparison among surgeons is particularly difficult. While the concept of measuring individual surgeon quality has a long history, technology now allows for new and innovative ways to measure and achieve surgical excellence. However, some recent efforts to make surgeon-level quality data publicly available have highlighted the challenges of this work. Through this chapter, the reader will be introduced to a brief history of surgical quality measurement, learn about the current state of quality measurement, and get a glimpse into what the future holds.
Keywords: surgical quality; technical skills; video-based assessment; surgical quality